Developing a framework to improve employee engagement leveraging by organisational culture in banks for developing countries: a case study from Libya (Tripoli banks) - Eseleni, Mohamed Mohamed (Cranfield University, 2017)
Many previous studies have identified factors that enable and inhibit engagement. However, (Abukhzam and Lee, 2010; Twati and Gammack 2009; Mohamed, 2013) To date, there has not been any detailed research which focuses on staff engagement despite the fact that the ‗people factor‘ is of central importance in organizational change leveraging by organizational culture. Thus far, the research that has been carried out on the Libyan banking sector focus has been limited to e-banking ,service quality and customer satisfaction (Elmayar, 2011; El-Shukri, 2007; Khafafa and Shafii, 2013). This research contributes to filling this gap by developing a validated framework for improving employee engagement in Libyan banking organisations, and identifying specific interventions to improve engagement. A pilot study preceded two fieldwork phases, all of which took place in Tripoli. The pilot study involved interviewing employees and managers from four Libyan banks to identify factors potentially relevant to organisational engagement. In the main study (phase I), a further 20 individuals, representing employees, managers and senior management, were interviewed from the same four banks, to identify enabler/inhibitors of employee engagement in Libyan banking organisations. In phase II, a focus group of seven bank staff were asked to categorise and rank enablers/inhibitors of employee engagement, discussing their answers. The results of this categorisation task formed the basis of the employee engagement framework developed by this research. Interventions to improve engagement were identified by reviewing relevant literature and case studies, and analysing interview and focus group data. Ten factors from the pilot study were identified as having an effect on employee engagement within Tripoli banks sector and from The main study interviewed a further 20 employees from the same banks in Tripoli. Further factors were identified, some of which overlapped with the findings of the pilot study The final framework consisting of 12 themes and 42 interventions was validated by a team of experts and can be used to improve engagement by targeting key organisational areas. This framework, the first of its kind in the Libyan context, provides a much-needed guide for organisations and managers working within the banking sector there. It may also be applicable to other organisational sectors, in Islamic cultures, regions and organisations.
Keywords: employee engagement; organisational culture; Libyan banking sector; constant comparison method; grounded theory